Analysis of the Draft Genome of the Red Seaweed Gracilariopsis chorda Provides Insights into Genome Size Evolution in Rhodophyta. (23rd April 2018) - Lee, JunMo; Yang, Eun Chan; Graf, Louis; Yang, Ji Hyun; Qiu, Huan; Zelzion, Udi; Chan, Cheong Xin; Stephens, Timothy G; Weber, Andreas P M; Boo, Ga Hun; Boo, Sung Min; Kim, Kyeong Mi; et al.
Abstract: Red algae (Rhodophyta) underwent two phases of large-scale genome reduction during their early evolution. The red seaweeds did not attain genome sizes or gene inventories typical of other multicellular eukaryotes. We generated a high-quality 92.1 Mb draft genome assembly from the red seaweed Gracilariopsis chorda, including methylation and small (s)RNA data. We analyzed these and other Archaeplastida genomes to address three questions: 1) What is the role of repeats and transposable elements (TEs) in explaining Rhodophyta genome size variation, 2) what is the history of genome duplication and gene family expansion/reduction in these taxa, and 3) is there evidence for TE suppression in red algae? We find that the number of predicted genes in red algae is relatively small (4, 803–13, 125 genes), particularly when compared with land plants, with no evidence of polyploidization. Genome size variation is primarily explained by TE expansion with the red seaweeds having the largest genomes. Long terminal repeat elements and DNA repeats are the major contributors to genome size growth. About 8.3% of the G. chorda genome undergoes cytosine methylation among gene bodies, promoters, and TEs, and 71.5% of TEs contain methylated-DNA with 57% of these regions associated with sRNAs. These latter results suggest a role for TE-associated sRNAs in RNA-dependent DNA methylation to facilitate silencing. We postulate that the evolution of genome size in red algae is the result of the combined action of TE spread and the concomitant emergence of its epigenetic suppression, together with other important factors such as changes in population size.